Online english learning: main problems and some ways to solve them - Amalia L. Kuregyan; Ekaterina A. Pertsevaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Nowadays distance learning (DL) has become a universal way of teaching students both technical and humanitarian disciplines. Any foreign language requires the mastering of a large number of teaching materials, this number increasing due to the language skills heterogeneity in each group and this requires the development of specific skills in each individual group of students. Hence, learning priorities must be correctly prioritized and the specific area of knowledge must be presented in details. This paper focuses on the main problems of the DL and some ways to overcome them. To observe the topic under consideration, research philosophy was chosen as a core method of scientific investigation. Comparative and qualitative analysis were used to understand and interpret definitions applied in the paper. In the process of DL, the authors have identified aspects that need to be taken into account when providing tasks for different levels groups. In this regard, reference is also made to the tasks and exercises that have proved to be very effective during the DL interaction with students.